That sounds so good : 100 real-life recipes for every day of the week - Music, Carla Lalli (Clarkson Potter/Publishers, 2021)
"100 recipes to match every real-life occasion from the beloved Bon Appetit food editor at large and James Beard Award-winning author of Where Cooking Begins. Everyone deserves to have recipes up their sleeves that they turn to again and again, and Carla Lalli Music believes that these recipes should not only match what's in your pantry, but also should fit every mood and scenario that life throws at you. Since Carla knows that we only cook what we have time for and choose recipes based on what's going to be realistic on a given day, the recipes in That Sounds So Good are organized by situations that we all find ourselves in: quick stovetop suppers and one-pot/one-pan meals for weeknights, nourishing salads and grain bowls if you want to be a little cleaner, and lazy lunches and all-day stews for the weekend. Readers can find recipes based on their own needs at any given moment, knowing that whatever they choose to cook, the food will be Carla to the core--bold, unique flavors with a straightforward method and swap-friendly ingredients. Through it all, Carla shares strategies that keep cooking effortless and quick, like using the time it takes for water to boil to pick the herbs or toast the nuts you'll use later"--